Über Geometrie homogenen Räumen - Vosilius, R.; Dreimanas, A. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Р. Восилюс. А. Дрейманас. О геометрии однородных пространствR. Vosylius, A. Dreimanas. Apie homogeninių erdvių geometriją